2017
DOI: 10.1016/j.ausmj.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Monopoly Effect in Brand Image Associations

Abstract: The Natural Monopoly is a robust empirical generalisation that describes the tendency for more popular brands to attract light users of the product category. This study shows that this pattern can also explain the underlying ‘trade-off’ between associations that consumers hold in memory for a specific brand vs. other brands, given the same range of category cues or category entry points (e.g., purchase or consumption situations, core benefits etc.). Specifically, the Natural Monopoly can be extended to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
4
10
0
Order By: Relevance
“…They found that heavier wine buyers in Greece tended to purchase large-share wine brands, whereas light buyers tended to buy small-share brands. Stocchi et al (2017) suggest the anomaly could be due to the unique nature of the very fragmented Greek market. Another study by Bassi (2011) examined buying metrics for beer brands in Italy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that heavier wine buyers in Greece tended to purchase large-share wine brands, whereas light buyers tended to buy small-share brands. Stocchi et al (2017) suggest the anomaly could be due to the unique nature of the very fragmented Greek market. Another study by Bassi (2011) examined buying metrics for beer brands in Italy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently Stocchi et al (2017) explored whether the NM effect occurs in brand image associations. That is, the extent to which large-market share brands dominate the brand perceptions of consumers with least knowledge of the product category.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations